The Compounds of Tuna-Shredded (Thunnus sp.) Fortified Banana Blossom Extracts’ Antioxidant Activity and Xanthine Oxidase Enzyme Inhibition Capacity: An In Vitro-In Silico Study - Heder Djamaludin; Hardoko Hardoko; Muhammad Dailami; Vivi Nurhadianty; Mohammad Sholeh Uluwwi; Novaldo Yuri Muhammad; Tristany Brighton Jorghi (Indonesian Journal of Chemistry, 2023)
Tuna is one of the fish source of nutrition for humans because it contains high-quality protein and omega-3 fatty acids, which are beneficial for health. Tuna can be processed into various products, such as tuna-shredded. But it still has a drawback, i.e., the lower-fiber content. To enrich the fiber of tuna-shredded, fortification with banana blossoms can be developed as functional food such as preventing gout arthritis. The aims of this study were to develop a diversified product of tuna-shredded fortified banana blossoms and to determine the antioxidant activity in vitro and anti-arthritis gout through inhibition of the xanthine oxidase (XO) enzyme in silico. The method used was a simple, completely randomized design. The formulation of tuna-shredded used fortification and active compounds analyzed by LC-HRMS. The antioxidant activity was analyzed by the DPPH. Inhibition of the XO enzyme was analyzed by molecular docking in silico. The results showed that tuna-shredded extract contained 32 compounds, which had total phenolic was 0.00134 mg GAE/g, total flavonoid was 0.0006670 mg QE/g, and IC50 was 4.38 ppm. Ferulic acid had the potential to inhibit the XO enzyme with binding affinity was -9.70 kcal/mol through hydrogen bonds and hydrophobic interactions.